Generation of a fluorescent mNeonGreen insulin reporter line in the H1 (WA01) hESC background - Karla F. Leavens; Catherine Osorio-Quintero; Elisabeth Ashlyne Yeuteuh; Francesca T. Perez-Profeta; Anna Ada Dattoli; Fabian L. Cardenas-Diaz; Deborah L. French; Paul Gadue (Stem Cell Research)
Over the past decade, the use of human stem cell-derived β cells (SC-β cells) to model pancreatic β cell development, function and disease has become increasingly common. Though protocols are rapidly improving, current directed differentiation strategies do not yield a pure population of insulin-positive SC-β cells in vitro. Therefore, it is experimentally advantageous to have reporter lines that allow for live sorting of insulin-positive populations. To aid in these studies, we have knocked mNeonGreen fluorescent protein into the endogenous insulin locus of the commonly used H1 (WA01) human embryonic stem cell line.